A novel energy efficient compression adsorption hybrid for higher COP - Kho, Desmond Jun Hong (2014)
To meet the rising global demand in energy, it is necessary to develop a sustainable cooling system. The hybrid adsorption cooling cycle is an example of the proposed sustainable cooling systems. The hybrid system uses the amalgamation of vapour compression and adsorption, employing silica gel-water as adsorbent-adsorbate pair. Compared to absorption refrigeration, silica gel-water adsorption refrigeration does not experience the problems of corrosion, crystallization and distillation. Due to non-isothermal supercritical heat rejection in the gas cooler, the CO2 based cooling cycle has unsatisfactory cooling capacity and low coefficient of performance. It is feasible to use the waste heat generated from the compressor of a CO2 cycle to drive an adsorption reactor. These combinations not only decrease the heat sink or condenser temperature of CO2 cycle, they also improve the overall COP. Given its effective cold production which relies upon waste heat and solar energy utilization, thermally driven cooling cycle plays a significant role in reducing energy consumption. The cycle simulation was based on the experimentally confirmed adsorption isotherms, kinetics and isosteric heat of adsorption data for silica gel-water. The optimum coefficient of performance (COP) and specific cooling power (SCP) were calculated in terms of cycle time, switching time, mass flow rate of CO2 and cooling water of condenser and temperature of heat source. The temperature profiles of the components were also plotted. Results showed that the combined adsorption cycles were feasible even when the low-temperature heat source was available. With the hybrid adsorption cooling system, the overall COP improved from 2.067 to 2.226.